Co-delivery of endometrial mesenchymal stem cells and macrophages with an electrospun patch suppresses endometrial fibrosis via IL-10 related signaling - An, Jiangru; Li, Shuhong; Ma, Tianyi; Chen, Yonghua; Santerre, J. Paul; Wang, Wenshuang; Ma, Peng; Zhang, Xiaoqing (Frontiers in Immunology, 2026)
IntroductionIntrauterine adhesion (IUA) is characterized by endometrial fibrosis with partial or complete obliteration of the uterine cavity due to adhesion of the uterine wall. Currently, there is lack of effective strategies to address IUA and a strategy that can resolve endometrial fibrosis is needed. Human endometrial mesenchymal stem cells (H-EMSCs) and macrophages (mø) both reside in endometrial tissues and are important for endometrial repair. However, whether co-delivery of H-EMSCs and mø using a biocompatible biomaterial platform could address endometrial fibrosis and enhance repair remains unknown.MethodsThis study developed a H-EMSCs-mø co-delivery system using an electrospun polycaprolactone-hyaluronic acid (PCL-HA) membrane and established a rat endometrial damage model. The effects of the co-delivery system on endometrial tissue fibrosis, M1 and M2 mø phenotypic marker modulation, and the pro-inflammatory (TNF-α) and anti-inflammatory (IL-10) factor production were investigated. The mechanisms involved in the interactions between H-EMSCs and mø were also delineated. All data were analyzed using analysis of variance with Tukey’s test for pair-wise comparisons or an independent samples t-test where appropriate.ResultsIn the rat endometrial damage model, H-EMSCs and mø co-delivery system (PCL-HA/H-E/mø) could significantly reduce endometrial fibrosis at day 14 after implantation vs. PCL-HA alone or H-EMSCs single-delivery (PCL-HA/H-E). In addition, PCL-HA/H-E/mø supported M1 (CD80, CD86) to M2-type mø phenotypic marker change and enhanced MSC marker (CD90) expression at days 3, 7 and 14, when compared to PCL-HA and PCL-HA/H-E groups. Moreover, PCL-HA/H-E/mø system had lower TNF-α gene expression but higher IL-10 gene and protein expression at day 7 post-implantation, suggesting an overall change from a more pro-inflammatory to a more wound-healing endometrial tissue microenvironment. In probing the mechanisms underlying the anti-fibrotic effect of the PCL-HA/H-E/mø system, it was found that IL-10 could have significantly reduced endometrial tissue fibrosis.DiscussionsCo-delivery system reduced fibrosis and supported an M1-type to M2-type overall change of the mø phenotypes in the endometrial tissue damage model. IL-10 was one of the important factors in inhibiting endometrial fibrosis in the co-delivery system. This study provided significant insights into using a co-delivery system PCL-HA/H-E/mø, to effectively alleviate endometrial fibrosis and potentially for a more effective treatment of IUA.